Survival outcome and impact of delayed imatinib therapy in gastric gastrointestinal stromal tumors - Jansuwan, R.; Samphao, S.; Chaochankit, Wongsakorn (Frontiers in Surgery, 2025)
BackgroundGastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract, with the stomach being the predominant site. Surgical resection is the primary treatment for localized disease, but recurrence remains a concern, particularly in high-risk patients. Tyrosine kinase inhibitors (TKIs), such as imatinib, improve disease-free survival (DFS), yet their accessibility is often limited in resource-constrained settings.MethodsThis retrospective cohort study included gastric GIST patients who underwent surgical resection between 2015 and 2020 at a tertiary referral center. DFS and overall survival (OS) were analyzed using Kaplan–Meier curves and Cox proportional hazards regression.ResultsA total of 86 patients were included, with 40 (46%) classified as high-risk. The 5-year DFS was significantly lower in high-risk patients (40% vs. 95.7%, p < 0.001). Imatinib therapy group was associated with worse DFS in high-risk patients (p = 0.003), likely due to delayed initiation after recurrence rather than adjuvant use. Significant predictors of poor DFS included smoking (p < 0.001), prolonged operative time (p = 0.034), and advanced tumor stage (p < 0.001).ConclusionDelayed imatinib therapy negatively impacts DFS in high-risk gastric GIST patients, highlighting the need for improved access to early TKI treatment. Additionally, smoking cessation and optimized perioperative management may enhance survival outcomes. Addressing modifiable risk factors and ensuring timely posoperative treatment could improve prognosis in this population.